PD-L1 Is Expressed and Promotes the Expansion of Regulatory T Cells in Acute Myeloid Leukemia - Dong, Yuqing; Han, Yixiang; Huang, Yisha; Jiang, Songfu; Huang, Ziyang; Chen, Rongrong; Yu, Zhijie; Yu, Kang; Zhang, Shenghui (Frontiers in Immunology, 2020)
Intratumoral accumulation of CD4+CD25+Foxp3+ regulatory T (Treg) cells occurs in acute myeloid leukemia (AML), but little is known about the role of tumor cells themselves in this process. Here, we showed that an immune checkpoint PD-L1 expressed by AML cells promoted the conversion and expansion of Treg cells sustaining high expression of Foxp3 and PD-1 as well as a suppressive function. Furthermore, an AML cell line HEL overexpressed PD-L1 promoted the conversion and expansion of Treg cells and CD4+PD-1+Foxp3+ T (PD-1+Treg) cells from the conventional CD4+ T cells. CD4+CD25highPD-1+ T cells secreted more IL-10 production than CD4+CD25highPD-1- T cells. IL-35, another cytokine secreted by Treg cells, promoted the proliferation of HL-60 cells and enhanced chemoresistance to cytarabine. Blockade of PD-1 signaling using anti-PD-L1 antibody dramatically impaired the generation of Treg cells and sharply retarded the progression of a murine AML model injected with C1498 cells. The frequency of intratumoral PD-1+ Treg cells was capable of predicting patient survival in patients with AML. In conclusion, our data suggest that PD-L1 expression by AML cells may directly drive Treg cell expansion as a mechanism of immune evasion and the frequency of PD-1+ Treg cells is a potential prognostic predictor in patients with AML.